2015
DOI: 10.15185/izawol.126
|View full text |Cite
|
Sign up to set email alerts
|

Sports, exercise, and labor market outcomes

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Physical activity is related to health improvements, 25,26 which may lead to better worker performance, thereby increasing labor productivity and earnings. 7,27 Physical activity may also facilitate social and professional networks, which promote career development and increase labor market returns. 7 Additionally, physical activity may develop cognitive [28][29][30] and non-cognitive skills, [31][32][33] which are rewarded later on in the labor market.…”
Section: Limitations and Strengthsmentioning
confidence: 99%
“…Physical activity is related to health improvements, 25,26 which may lead to better worker performance, thereby increasing labor productivity and earnings. 7,27 Physical activity may also facilitate social and professional networks, which promote career development and increase labor market returns. 7 Additionally, physical activity may develop cognitive [28][29][30] and non-cognitive skills, [31][32][33] which are rewarded later on in the labor market.…”
Section: Limitations and Strengthsmentioning
confidence: 99%
“…In addition to the positive correlation with health, physical activity has also been linked to positive returns in the labor market. There is evidence that former high school and college athletes (5,10,11,23,36) as well as those who are physically active in adulthood (14,17,(19)(20)(21)31) typically perform better in the labor market in terms of wages (5,10,11,19,23,31) and employment probability (17,36). For example, using information from a long-term perspective, Lechner (20) and Rooth (31) showed that physical activity was positively related to monthly earnings and hourly wages, and Hyytinen and Lahtonen (14) reported similar results for men on the basis of twin data.…”
mentioning
confidence: 99%
“…Although a positive connection between physical activity and labor market outcomes has been established, the reason for this correlation is unclear. One possibility is that higher physical activity leads to health gains, which, in turn, increase worker productivity and, therefore, labor market returns (20,21). Productivity gains can arise, for example, from decreased absences due to sickness or from better performance by workers.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Sport participation is generally considered to provide a multitude of positive benefits to individuals and society including but not limited to (i) reductions in crime (ii) increases in social capital and social integration (iii) improvements in health through physical activity and (iv) improvements in education outcomes. Studies examining the impact of sport participation on happiness (Huang & Humphreys, 2012), future income (Dewenter & Giessing, 2015), labour market outcomes (Lechner, 2015) have generally found sport participation to provide societal benefits. However, despite these widely held beliefs regarding the positive impact of sport participation on education, health and social issues, the results of studies investigating the relationship between sports participation and crime tend to be ambiguous.…”
Section: Introductionmentioning
confidence: 99%